Nova LMC 2009a as observed with XMM–Newton, compared with other novae. Issue 3 (21st May 2021) - Orio, Marina; Dobrotka, Andrej; Pinto, Ciro; Henze, Martin; Ness, Jan-Uwe; Ospina, Nataly; Pei, Songpeng; Behar, Ehud; Bode, Michael F; Her, Sou; Hernanz, Margarita; Sala, Gloria
ABSTRACT: We examine four high-resolution reflection grating spectrometers (RGS) spectra of the February 2009 outburst of the luminous recurrent nova LMC 2009a. They were very complex and rich in intricate absorption and emission features. The continuum was consistent with a dominant component originating in the atmosphere of a shell burning white dwarf (WD) with peak effective temperature between 810 000 K and a million K, and mass in the 1.2–1.4 M⊙ range. A moderate blue shift of the absorption features of a few hundred km s −1 can be explained with a residual nova wind depleting the WD surface at a rate of about 10 −8 M⊙ yr −1 . The emission spectrum seems to be due to both photoionization and shock ionization in the ejecta. The supersoft X-ray flux was irregularly variable on time-scales of hours, with decreasing amplitude of the variability. We find that both the period and the amplitude of another, already known 33.3-s modulation varied within time-scales of hours. We compared N LMC 2009a with other Magellanic Clouds novae, including four serendipitously discovered as supersoft X-ray sources (SSS) among 13 observed within 16 yr after the eruption. The new detected targets were much less luminous than expected: we suggest that they were partially obscured by the accretion disc. Lack of SSS detections in the Magellanic Clouds novae more than 5.5 yr after the eruption constrains the average duration of the nuclear burning phase.